Kissa literature from the Shyamkashi Press collection, Mathura, U.P. - Pritchett, Frances W., 1947-
Collection on microfilm of South Asian popular literature in Hindi, Urdu, and related dialects. Consists primarily of qissah (narrative "chapbook" literature)